Volume Measuring System Using Arduino for Automatic Liquid Filling Machine - M. H., Muhammad Sidik; S. A., Che Ghani (Research India Publications, 2017)
Food industry is one of the most important industry in order to make sure all of human being keep existed on this earth. By using automatic machine, quality and quantity of the product can be improved and even the profit can be increased. But automatic filling machine that available on market is complicated and difficult to clean up due to installation of cylinder piston that need pneumatic system to operate. In order to make it simple and easy to clean up, a new water volume measuring system using ultrasonic sensor developed to replace cylinder piston. An additional tank called measuring tank with ultrasonic sensor installed to measure the volume of water as desired before fill up inside the bottle. Two solenoid valve to control flow of water between storage tank to measuring tank and measuring tank to nozzle. Combinations between solenoid valve and ultrasonic sensor able to perform as well as cylinder piston and reduce the complexity of the machine. Besides that the cost this new system is very low and it can be implemented by small beverage company to boost up their production and profit.